Education: Quality VS Quantity. A Challenge to Link an d Match Policy - Emi Zulaifah (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 1996)
The issue on Indonesia's Education has mostly been looked upon from quantitative point of view. Many report on human resources develop ment, especially through the educational agents, relied their analysis on educational development quantitatively. Later in this writing, I refer this orientation as quantity oriented education. As an agent of people development, quantity orientation in education is facing a critical point regarding its ability to prepare human resources for a new era of International competition.